Efektivitas Gaming Addiction Awareness Programme (GAME) sebagai Intervensi Preventif Berbasis Komunitas dalam Mencegah Kecanduan Game Online pada Siswa Sekolah Dasar - Sri Ayu Mutmainah Kurniawati; Sitti Rojiyah Nur Insyirah Puhi; Irsyad; Ridha Habibah (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study evaluated the effectiveness of the Gaming Addiction Awareness Programme (GAME) as a community-based intervention to increase knowledge and awareness of online gaming addiction among 41 elementary school students. Using a one-group pretest–posttest quasi-experimental design, the results showed a significant increase in knowledge scores (t = -9.348; p < 0.05). Qualitatively, there was an increase in student awareness, understanding among teachers and parents, and the emergence of school policies restricting mobile phone use. These findings indicate that an integrative community approach is effective in improving literacy and supporting the prevention of online gaming addiction in children.